Perlakuan Akuntansi Biaya Lingkungan Pada Perusahaan Farmasi (Studi Pada PT. Sumber Obat Malang) - Putri, Syehryl Meidiana; Alamsyah, Ahmad Fahrudin (Jurnal Riset Akuntansi Politala, 2024)
This study aims to determine the accounting treatment of environmental costs in waste management efforts at PT Sumber Obat related to the process of identification, recognition, measurement, presentation, and disclosure of environmental costs. This research uses qualitative research methods with a case study approach. The results showed that PT Sumber Obat has carried out waste management very well and also pays attention to its responsibility to the surrounding community by holding CSR programs. In the application of environmental accounting, there are five stages of cost allocation. The identification stage is classified into 2 costs, namely operational costs (repair costs, maintenance costs, employee bonus salaries, chemical decomposition costs, administrative and general costs, donation costs) and environmental and AMDAL handling costs. The environmental cost recognition stage uses the accrual basis method which recognizes when transactions occur without reference to cash transfers. The measurement stage of environmental costs is by PSAK which uses rupiah units and uses the historical cost method. The presentation stage of environmental costs has not been separated from the financial statements and is made one with the company's operating costs included in the income statement. The disclosure stage shows that PT Sumber Obat has not disclosed related environmental cost reports, and there are no policies and notes related to environmental costs in the notes to the financial statements.